2019
DOI: 10.17358/jabm.5.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Keberhasilan E-Learning Dalam Perspektif Sistem Informasi (Studi Kasus Universitas Terbuka)

Abstract: As a pioneer in e-learning implementation, UT is required to be able to provide an adequate information technology system continuously, particularly to reach an extensive area of Indonesia. The purpose of this study was to asses of e-learning implementation and to evaluate the factors that influenced e-learning at UT using the DeLone and McLean information system models. Data was collected using a structured questionnaire among two respondent categories, namely students and lecturers, using a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 9 publications
0
12
0
12
Order By: Relevance
“…Dimensi kualitas layanan yaitu; kegunaan, mudah digunakan, hiburan, hubungan komplementer, pelayanan pelanggan, dan interaksi pembeli-penjual berpengaruh sangat signifikan terhadap kepuasan pelanggan (Manalu et al 2007). Kualitas informasi, kualitas sistem, dan kualitas layanan berpengaruh positif terhadap kepuasan pengguna aplikasi e-learning (Rahmat et al 2019). Memperkuat hubungan dengan pelanggan dalam menciptakan kepuasan, sangat dipengaruhi oleh keseluruhan layanan yang disiapkan yang memperhatikan aspek-aspek yang diharapkan, dirasakan pelanggan, atau yang diterimanya dari jasa yang diterima oleh pelanggan (Hannan, 2014).…”
Section: Pendahuluanunclassified
“…Dimensi kualitas layanan yaitu; kegunaan, mudah digunakan, hiburan, hubungan komplementer, pelayanan pelanggan, dan interaksi pembeli-penjual berpengaruh sangat signifikan terhadap kepuasan pelanggan (Manalu et al 2007). Kualitas informasi, kualitas sistem, dan kualitas layanan berpengaruh positif terhadap kepuasan pengguna aplikasi e-learning (Rahmat et al 2019). Memperkuat hubungan dengan pelanggan dalam menciptakan kepuasan, sangat dipengaruhi oleh keseluruhan layanan yang disiapkan yang memperhatikan aspek-aspek yang diharapkan, dirasakan pelanggan, atau yang diterimanya dari jasa yang diterima oleh pelanggan (Hannan, 2014).…”
Section: Pendahuluanunclassified
“…This research uses the e-learning theory previously conducted by Marlina [8], Riyanda et al [9], Rahmat et al [10], and Nirsal et al [11] which can be concluded that in the teaching and learning process using the e-learning method, the organizational environment, aspects of human resource competence, clarity of information, and systems and services that can create a learning process must be prepared for a better teaching without them having to be face to face and can be done anywhere and at a time limit. In addition, this research also seeks to evaluate the online lecture policy using four of the five indicators put forward by Agustino [12], namely:…”
Section: Indicator-policy Evaluation Indicatormentioning
confidence: 99%
“…Berbagai metode untuk melakukan evaluasi juga digunakan, metode yang dipilih tentunya kembali pada tujuan evaluasi itu sendiri. Beberapa metode misalnya COBIT [23,22]; Hot-Fit [27]; SMART dan DEA [21,29]; PIECES Framework [31]; UTAUT [32], TAM [39]; DeLone dan McLean [40,28]; AHP [17]; Teknik Usability [41]; Pendekatan utility system [20]. Sementara kriteria-kriteria dibangun untuk misalnya mengukur persepsi, keefektifan, fungsi, dan benefit dilakukan oleh beberapa peneliti berikut [13,14,16,18,19,34,37,30].…”
Section: No Penulisunclassified